Estimating the Effects of Corruption : Implications for Bangladesh - Rahman, Aminur (World Bank, Washington, DC, 2014)
Building on the pioneering work of Barro (1991) and Mauro (1995) to include the most recent years for which data are available (for Bangladesh in the 1990s), the authors investigate the relationships between corruption, and growth, and, between corruption and investment, both domestic and foreign, to see whether they have changed from earlier decades. Then they move away from Mauro's implicit assumption that the corruption index value for a relatively short period of time, can be used as a proxy for the long run, and further augment Mauro's model by including significant regional dummy variables, in an attempt to take account of various region-specific effects. The authors also analyze the sensitivity of corruption in the presence, and absence of various policy, geographic, and demographic variables that are widely used in empirical growth, and investment literature. The findings suggest that countries serious about improving governance, and reducing corruption, should redefine the role of government, overhaul the system of incentives, and strengthen domestic institutions, to make sure the necessary checks, and balances are in place. Such an approach to reform would help attract more investment - both domestic and foreign - and would accelerate economic growth, and poverty reduction.